PEMBELAJARAN BERNYANYI SECARA UNISONO BERDASARKAN KURIKULUM 2013 DI SMP 4 BUKITTINGGI - Saputra, Heri; Lumbantoruan, Jagar (SENDRATASIK UNP, 2019)
Abstract                 This study aims to describe Unisono Singing Learning Based on the Curriculum 2013in SMP Negeri 4 Bukittinggi.This type of research was qualitative with using a descriptive analysis method approach. The main instrument in this study was the researcher and was assisted by supporting instruments such as stationery and camera. The type of data used primary and secondary data. Techniques of data collection were carried out by taking literature study, observation, and documentation study. The steps in analyzing data were done by reducting, presenting and drawing data conclusions.The result shows that theUnisono singing learning which is conducted by teacher at class VII in SMP Negeri 4 Bukittinggi can be concluded that the lesson plan must be guided to the formulation of learning that should contains cognitive, affective, psychomotor and its implementation is adjusted to the students’ characteristics and the learning outcomes are still not optimal because the learning design is not standard and the implementation is not optimal yet so that the students cannot sing unisono as expected. Keywords: learning, Unisono, curriculum 2013